The Impact of Donald J. Trump’s Egocentric Policies on Indonesia: A Neorealist Analysis (Case Study: The 2024–2025 Trade War) - SEPTIAWAN, YUDI; Jamal, Din Aulia; Muhammad, Amir Yusuf; Endah, Kurniati (Indonesian Journal of Global Discourse, 2025)
This study analyses the impact of the United States' foreign policy under Donald Trump on Indonesia, with particular attention to the trade war during the 2024–2025 period. Utilizing a Neorealist theoretical framework, the analysis highlights the significance of national interests, global power distribution, and international system dynamics in shaping bilateral relations. The "America First" policy advanced by Trump prioritizes domestic interests, often at the expense of partner countries. The trade war case study indicates that the United States' protectionist policies and economic sanctions placed significant pressure on Indonesia's export sector, especially in manufacturing and strategic commodities. In response, Indonesia adjusted economic policies and engaged in bilateral diplomacy to maintain national stability. The findings indicate that, within a Neorealist context, states such as Indonesia should strengthen their bargaining power and diversify economic partnerships to navigate an anarchic international system dominated by major powers.